Correlation Between Soil Macrofauna and Soil Chemical Properties in Smallholder Palm Oil Plantations - Pratama, Raharya; Sulakhudin; Leony Agustine (Talenta Publisher, 2025)
Writing This study aimed to determine the relationship between soil macrofauna communities and soil chemical properties in smallholder oil palm plantations. Field sampling and laboratory analyses were conducted at five observation points arranged diagonally. Soil macrofauna were collected using two methods: the pitfall trap method for surface-dwelling organisms and the monolith method for subsurface organisms. Observed parameters included population abundance, species diversity and richness, organic carbon (C-organic), total nitrogen (N-total), available phosphorus (P), and exchangeable potassium (K-dd). Data were tested for normality and linearity prior to correlation analysis. The results from the pitfall trap method showed that pygmy grasshoppers (Tetrigidae) were strongly correlated with C-organic (r = 0.757) and N-total (r = 0.677), while termites (Termitidae) also showed strong correlations with C-organic (r = 0.612) and N-total (r = 0.553). Carpenter ants (Formicidae) exhibited negative correlations with all soil nutrients, whereas black garden ants (Formicidae) showed a strong positive correlation with available P (r = 0.604). Only one species was found using the monolith method; therefore, no further analysis was conducted. Overall, macrofauna diversity and species richness showed very strong correlations with C-organic and N-total (r > 0.94), and strong correlations with K-dd (r = 0.860). These findings indicate that the availability of organic carbon, nitrogen, and potassium plays a crucial role in shaping soil macrofauna community structure in smallholder oil palm plantations.